Size- and shape-dependent photocatalysis of porphyrin nanocrystals. (11th March 2019) - Li, Qi; Zhao, Nana; Bai, Feng
Abstract: Abstract : The design and engineering of the size and shapes of photoactive building blocks enable the fabrication of functional nanocrystals, especially for applications in light harvesting, photocatalytic synthesis, water splitting, and photodegradation. Synthesis of such nanocrystals has been demonstrated recently through noncovalent interactions such as π–π stacking and ligand coordination using optically active porphyrin as a functional building block. Depending on the kinetic conditions, the resulting nanocrystals exhibit well-defined one- to three-dimensional shapes such as spheres, nanowires, and nano-octahedra. These well-defined porphyrin nanocrystals show interesting size- and shape-dependent photocatalytic activity. This article reviews the synthesis and formation of porphyrin nanocrystals with controlled size and shape. Important photocatalytic processes such as photodegradation of organic pollutants, photocatalytic water splitting and hydrogen production, and photosynthesis of metallic fuel-cell catalysts are highlighted. Insights on size- and shape-dependent properties are discussed.